Cannabidiol (CBD) in Dietary Supplements: Perspectives on Science, Safety, and Potential Regulatory Approaches. (2nd September 2020) - Walker, Larry A.; Koturbash, Igor; Kingston, Rick; ElSohly, Mahmoud A.; Yates, Charles Ryan; Gurley, Bill J.; Khan, Ikhlas
Abstract: The proliferation in the last few years of cannabidiol (CBD)-containing products in the U.S. markets has been greatly accelerated by changes in the regulatory environment, and by perceptions of their health benefits and presumed safety. The result has been aggressive marketing of many types of products, some of dubious quality, making or implying drug-type claims. The recent approval by the U.S. Food and Drug Administration (FDA) of CBD in the form of Epidiolex®, further complicates the regulatory picture. In addition, a number of studies suggest that, at least at high doses, there may be serious adverse effects or drug interactions associated with CBD. At present, CBD-containing products do not meet the strict definition of dietary supplements, but the FDA is continuing to consider some framework under which they might be allowed. Meanwhile, FDA has adopted a "risk-based" enforcement policy. Possible approaches to a new framework for regulation of CBD products as dietary supplements are discussed here, including expanded research emphasis, a robust corporate stewardship program, and a rigorous adverse event reporting program.